Halal Supply Chain Traceability System Modeling in Maintaining the Integrity of Halal Food Products With Interpretive Structural Modeling (ISM) Approach - Haryono Haryono; Dwi Iryaning Handayani (PROZIMA (Productivity, Optimization and Manufacturing System Engineering), 2018)
Fraud of fake halal label products does not open halal production processes about the supply chain from upstream to downstream. Therefore, in product integrity agreements, it is necessary to implement traceability in the food supply chain as an effective tool in ensuring product halalness and ensuring food products are safe. Therefore, this study tries to make a model of halal Supply Chain Traceability in the integrity agreement of halal food products. The method used in modeling the halal supply chain traceability system using Interpretive Structural Modeling (ISM). Elements of a halal supply chain tracking system, in addition to halal procurement, halal manufacturing, halal logistics, halal distribution, supplier traceability, producer traceability, logistics traceability, distribution traceability. ISM Modeling results in the integration of halal products are located in Quadran IV Driver Power with halal manufacturing, producer traceability, supplier traceability, Quadran III Strong-Very Driver Depends on Variables (Linkage), Traceability system elements of the halal supply chain that are in accordance with this Quadran will be sought integrity of halal products and has strong advantages as a driver, this quadrant contains halal procurement, traceability distribution, halal logistics. Whereas the halal supply chain traceability system that is not related to the integrity of halal products comes in. Quadran II Driver Power namely: halal logistics and distribution traceability.